Incidence and natural history of pure red cell aplasia in major ABO‐mismatched haematopoietic cell transplantation. (18th January 2013) - Aung, Fleur M.; Lichtiger, Benjamin; Bassett, Roland; Liu, Ping; Alousi, Amin; Bashier, Qaiser; Ciurea, Stefan O.; de, Marcos J.; Hosing, Chitra; Kebriaei, Partow; Nieto, Yago; Oran, Betul; et al.
Summary Major ABO mismatching is not considered a contraindication to allogeneic haematopoietic stem cell transplantation (HSCT). Modern reduced‐intensity conditioning and reduced‐toxicity regimens cause much less myeloablation than conventional myeloablative regimens, such as cyclophosphamide with busulfan or total body irradiation, which may affect the incidence of pure red cell aplasia (PRCA). We estimated the incidence and described the natural history of PRCA in patients with major ABO‐mismatched donor stem cells. Between 2007 and 2008, 161 (27% of all patients undergoing HSCT) underwent allogeneic HSCT with major ABO‐mismatched stem cells and 12 (7·5%) of these patients developed PRCA. Thirty and ninety day T‐cell and myeloid cell chimerism and neutrophil and platelet engraftment did not differ between patients who developed PRCA and those who did not. The only risk factor associated with PRCA was the use of a fludarabine/busulfan conditioning regimen. All patients with PRCA needed red cell transfusion for several months after HSCT resulting in significant iron overload. Pure red cell aplasia resolved spontaneously in the majority (seven patients) but only resolved after stopping tacrolimus in three patients. Hence, after major ABO‐mismatched HSCT, the incidence of PRCA was 7·5% and it resolved spontaneously or after withdrawal of immunosuppression in the majority of patients.